Influence of Obesity and Type 2 Diabetes on Chemotherapy Response in Ovarian Cancer Patients Receiving Carboplatin– Paclitaxel - Ibrahim Dahy, Ahmed Abdulraheem; Saeed, Baraa Ahmed; Salem Alsafar, Ashraf Raad; Jaber Faisal, Anwer (Asian Pacific Journal of Cancer Biology, 2026)
Background and Aim: Ovarian cancer is one of the leading causes of cancer death in the gynecologic sector across the globe. There is growing evidence to indicate that obese patients and those with Type 2 diabetes mellitus (T2DM) could have a biological effect on tumors and chemotherapy outcomes. The aim of the study was to determine how obesity and T2DM affect inflammatory, glycemic, and tumor markers of women whose ovarian cancer has Stage II and who are treated with Carboplatin-Paclitaxel chemotherapy. Methods: A total of 105 women were recruited and classified into three groups: Group 1 (normal BMI, non-diabetic), Group 2 (obese and have Type 2 diabetes mellitus), and Group 3 (overweight and have Type 2 diabetes mellitus). Serum measurements made in the hs-CRP, IL-1β, CA-125, fasting plasma glucose (FPG), and HbA1c were measured once during the third chemotherapy cycle. The results were presented as Mean ± SE and compared across groups. Results: Group 2 and Group 3 had significantly higher levels of inflammatory markers (hs-CRP and IL-1β) and glycemic markers (FPG and HbA1c) than Group 1. Group 3 also depicted much greater glycemic values in comparison to Group 2. The groups were also much higher in CA-125 in the diabetic groups in comparison with Group 1. No statistically significant difference in CA-125 was, however, found between Groups 2 through 3, although both had higher values compared to Group 1. This trend could indicate a less significant decrease in tumor marker levels in the patients with a metabolic poor health state, which could indicate a less potent biochemical response to chemotherapy. Conversely, the CA-125 levels of Group 1 were nearer to the normal range, which means that the chemotherapy response was more promising. Conclusion: Systemic inflammation and poor glycemic control associated with obesity and T2DM in patients with ovarian cancer undergoing chemotherapy. The consistent increase of CA-125 in the diabetic populations regardless of the general treatment may indicate decreased chemotherapy response, which will validate the arising correlation between metabolic dysfunction and chemoresistance. An essential supplement to oncologic management may thus be metabolic health optimization.